MODERN DISPLAY METHODS IN LABORATORY LECTURES OF THE COURSE LASER TECHNOLOGIES BASICS - CHMELICKOVA, Hana; LAPSANSKA, Hana; HIKLOVA, Helena; HAVELKOVA, Martina (Trends in education, 2009)
This contribution introduces immediate graphical display experiment results with metal and non-metal materials, affected by high-power solid-state laser radiation. Structural changes can be observed by CCD camera directly in the working point. Affected surface profile is scanned by contact profilometer TALYSURF, Confocal microscope LEXT displays details with maximal magnification 14 400 times. These methods will significantly complete experimental lectures of the new course Laser technologies basics - Study programme Physics, bachelor type, field of study Instrument Physics.
Keywords: education; experiment; laser; display.